De generatie van 1900 in Nederland en België. - Alberigs, L. M.; Redeker, Hans; Vanbeselaere, W. (Venlo (NL) : Van Spijk Art Projects Venlo, 1979)
Andriessen, Mari ; Buning, Johan ; Dasnoy, Albert ; Delvaux, Paul ; Van Dyck, Albert ; Grard, George ; Hendrickx, Jos ; Hynckes, Raoul ; de Kat, Otto ; Ket, Dick ; Koch, Pyke ; Langeweg, Ger ; Leplae, Charles ; van Leusden, Willem ; Magritte, René ; Mair, Jacques (Jaap) Le ; Malfait, Hubert ; Mekkink, Johan ; Moesman, J.H. ; Oldeboerrigter, Melle ; Onnes, Harm Kamerlingh ; Ouboter, Ru de Bruyn ; Van Overstraeten, War ; van Pallandt, Charlotte ; Röling, B.V.A. ; Schuhmacher, Wim ; Vandewalle, Adriaan ; Verdegem, Jos ; Verwey, Kees ; Vinck, Jozef ; Wezelaar, Han ; Willink, Carel ; Wolvens, Henri-Victor
Bibliografie
Biografie
Nederlands
boek
Keywords: België; Nederland